The Process Characteristics of Rapid Freezing: Continuous and Discrete Heat Removal Method - Neverov E.; Lifenceva L.; Usov A. (Техника и технология пищевых производств)
The research features the rational conditions of the process of rapid freezing for unpackaged small-sized foods by the method of continuous and discrete heat sink. The paper presents a graphical interpretation of the calculations of the average volume temperature for various temperature regimes that are used to freeze semi-finished products. The method makes it possible to determine the temperature at any time. The experiment defined the most rational range of air circulation speeds with a continuous heat sink in the range from 4 m/s to 6 m/s. The article features curves of changes in temperature and heat flux density during the rapid freezing of small-sized semi-finished meat products. They show the nature of the changes in the air coefficient of the meat sample heat transfer curves and the medium velocity of the object air. An increase in the heat flux density and a reduction in the duration of freezing by about 1.4 times occurred when the temperature of the cooling medium decreased from –20°C to – 40°C at an air speed of 6 m/s. The research determined the process characteristics of rapid freezing in continuous mode using a discrete heat sink. The authors describe the comparative characteristics of the change in the duration of the freezing process and the speed of the process with continuous and discrete heat sinks. The study presents the curves of changes in temperature and heat flux density during rapid freezing of small-sized semi-finished meat products, depending on the conditions of heat transfer. When a discrete heat sink was used, the duration of the freezing process was fpund to be 20 min, while with a continuous heat sink it lasted 26 min. The paper also includes a thermogram and the kinetics of heat sink during freezing in discrete conditions, as well as a software program for quick freezing of semi-finished minced meat products. The indicators of the meat quality are considered depending on the conditions of the heat sink, as well as the change in the physicochemical properties of the product after freezing and during storage. Studies of quality indicators of small-sized semi-finished meat products were carried out in the laboratory of the scientific-innovative enterprise «Sibagropererabotka» (Novosibirsk, Russia).